Drug repurposing to tackle parainfluenza 3 based on multi-similarities and network proximity analysis - Chen, Xinyue; Zhou, Bo; Jiang, Xinyi; Zhong, Huayu; You, Aijing; Zou, Taiyan; Zhou, Chengcheng; Liu, Xiaoxiao; Zhang, Yonghong (Frontiers in Pharmacology, 2024)
Given that there is currently no clinically approved drug and no vaccine for parainfluenza 3(PIV3), we applied a drug repurposing method based on disease similarity and chemical similarity to screen 2585 clinically approved chemical drugs using PIV3 potential drugs BCX-2798 and zanamivir as our controls. Twelve candidate drugs were obtained after screened with good disease similarity and chemical similarity (S>0.50, T>0.56). When docking them with the PIV3 target protein, hemagglutinin-neuraminidase (HN), only oseltamivir was docked with a better score than BCX-2798, which indicates that oseltamivir has indeed an inhibitory effect on PIV3. After the distance (𝑍𝑍 𝑑𝑑𝑑𝑑 ) between the drug target of 14 drugs and the PIV3 disease target were measured by the network proximity method based on the PIV3 disease module, it was found that the 𝑍𝑍 𝑑𝑑𝑑𝑑 values of amikacin, oseltamivir, ribavirin and streptomycin were less than those of the control. Then, oseltamivir is the best potential drug because only it met all above screening requirements. Additionally, to explore whether oseltamivir bind to HN stably, molecular dynamics simulation of oseltamivir binding to HN was proceed and the results showed that the RMSD value of the complex tended to be stable within 100ns, and the binding free energy of the complex was low (-10.60 kcal/mol). It was proved that oseltamivir screened by our drug repurposing method had the potential feasibility of treating PIV3.